1995
DOI: 10.1021/jm00010a029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure-Activity Relationships of Side-Chain-Substituted Analogs of the Allylamine Antimycotic Terbinafine Lacking the Central Amino Function

Abstract: Terbinafine is a therapeutically used inhibitor of fungal squalene epoxidase that has prompted extensive derivatization programs for structure-activity relationship studies. In the present study, derivatives of terbinafine were synthesized that lack the central tertiary amino group but have polar substitutents at the tert-butyl residue of the side chain. Evaluation of the antifungal potential revealed that representatives of this novel structural type can also exhibit broad antifungal activity, indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 5 publications
0
42
0
Order By: Relevance
“…Bacterial salicylate 1-monooxygenase catalyzes the formation of catechol from salicylate, an intermediate from naphthalene degradation (2). Thus, terbinafine, which has a naphthalene nucleus in its chemical structure (23)(24)(25)39), could be the substrate for a similar degradation pathway in fungi, generating salicylate or an analogous compound as substrate for the enzyme salicylate 1-monooxygenase in A. nidulans.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial salicylate 1-monooxygenase catalyzes the formation of catechol from salicylate, an intermediate from naphthalene degradation (2). Thus, terbinafine, which has a naphthalene nucleus in its chemical structure (23)(24)(25)39), could be the substrate for a similar degradation pathway in fungi, generating salicylate or an analogous compound as substrate for the enzyme salicylate 1-monooxygenase in A. nidulans.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of compounds 4a-d and 5a-d was carried out from the reaction of acetylene 1 with butyl lithium and the subsequent reaction with the corresponding electrophile agent 3, in the presence of 2 mol-equiv of BF 3 •OEt 2 (Scheme 1). Firstly, the lithium acetylenides were generated from the respective acetylenes 1,2 using BuLi in THF, at -20 °C for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the lithium acetylenides were generated from the respective acetylenes 1,2 using BuLi in THF, at -20 °C for 30 min. In a second step, the reaction between β-dimethylaminovinyl ketones 3 and lithium acetylenides was carried out using BF 3 •OEt 2 , -15 °C for 2 hours, and THF as solvent. The transformation was completed after being stirred at room temperature for 16 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have variously reported the elimination half-life of terbinafine in humans to be 15 h (33), 26 h (27), 290 h (35), and 22 days (33,35,43). Terbinafine is extensively metabolized in the liver by oxidation or N demethylation of the three carbon atoms bound to the central nitrogen atom or of the nitrogen atom itself (2), and the metabolites lack the antimycotic activity of the parent drug (34).…”
mentioning
confidence: 99%